2019
DOI: 10.1073/pnas.1913232116
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the zinc-finger antiviral protein in complex with RNA reveals a mechanism for selective targeting of CG-rich viral sequences

Abstract: Infection of animal cells by numerous viruses is detected and countered by a variety of means, including recognition of nonself nucleic acids. The zinc finger antiviral protein (ZAP) depletes cytoplasmic RNA that is recognized as foreign in mammalian cells by virtue of its elevated CG dinucleotide content compared with endogenous mRNAs. Here, we determined a crystal structure of a protein-RNA complex containing the N-terminal, 4-zinc finger human (h) ZAP RNA-binding domain (RBD) and a CG dinucleotide-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
174
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(183 citation statements)
references
References 26 publications
6
174
3
Order By: Relevance
“…RNA transcripts of an E7 viral cDNA with an UpA-high insert in the coding region showed a 1000-fold greater binding to ZAP compared to WT sequences, similar to that observed for a similarly constructed CpG-high viral RNA (1). While co-crystallisation of ZAP with CpG-high ligands (22,23) has recently provided information on the interaction of the zinc finger domains with CpG dinucleotides (and the stoichiometry of bases surrounding the motif), it is conceivable that UpA, as a similarly shaped pyrimidine (Y) -purine (R) dinucleotide might fit into the binding site. This degree of target flexibility would imply that other YpR dinucleotides (UpG and CpA) might be also recognised.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…RNA transcripts of an E7 viral cDNA with an UpA-high insert in the coding region showed a 1000-fold greater binding to ZAP compared to WT sequences, similar to that observed for a similarly constructed CpG-high viral RNA (1). While co-crystallisation of ZAP with CpG-high ligands (22,23) has recently provided information on the interaction of the zinc finger domains with CpG dinucleotides (and the stoichiometry of bases surrounding the motif), it is conceivable that UpA, as a similarly shaped pyrimidine (Y) -purine (R) dinucleotide might fit into the binding site. This degree of target flexibility would imply that other YpR dinucleotides (UpG and CpA) might be also recognised.…”
Section: Introductionsupporting
confidence: 61%
“…These findings suggest that there may be specifically favoured bases around the CpG binding ZAP that promotes binding. It is indeed intriguing, although not commented on in the studies, that both currently published structures of RNA bound to ZAP have U residues 5' to CpG (23) or at both 5' and 3'U sites (22), perhaps selected from other candidates because of their propensity to co-crystallise with ZAP.…”
Section: Alternative Dinucleotides and Cpg Context And Attenuation / mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study using a focused siRNA screen identified ZAPS and TRIM25 as host factors responsible for inhibition of HIV-1 constructs with artificially raised CpG dinucleotide frequencies and it was shown that ZAPS specifically binds to RNA sequences at CpG dinucleotide motifs 13 . The molecular mechanism for this binding has now been established through X-ray crystallography of the ZAP RNA binding domain complexed with a target CpG RNA, which demonstrates the second of four zinc fingers creates a highly basic patch that is required for specific binding of CpG dinucleotides 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian ZAP is expressed in two major isoforms, ZAPS (short) and ZAPL (long) which are generated by differential splicing, with ZAPL encoding an additional catalytically inactive poly (ADP-ribose) polymerase (PARP) domain 12 . ZAP had previously been identified as a host antiviral factor and is capable of binding to viral RNA through a pocket created by the second of four zinc fingers within the RNA binding domain 1315 . TRIM25 is an E3 ubiquitin ligase and member of the tripartite motif (TRIM) family, many of which have been associated with antiviral functions 16,17 .…”
Section: Introductionmentioning
confidence: 99%